Management of Drought Emergency Response Through the “Air Disuntik Resahpun Terobati” Program at the Perusahaan Air Minum Tirta Mangkaluku Kota Palopo - Johansyah, Oky Nur Pratiwi; Purnomo, Eko Cahyo; Darwis, Muh. (PINISI Discretion Review, 2024)
The purpose of this research is to find out 1) How is the Management of Drought Emergency Response Management through the Air disuntik Resahpun Terobati Program at Perusahaan Air Minum Tirta Mangkuluku of Palopo City; 2) Supporting and inhibiting factors in carrying out drought emergency response through the Air disuntik Resahpun Terobati Program at Perusahaan Air Minum Tirta Mangkuluku in Palopo City. This type of research is qualitative descriptive. Data collection by means of observation, interviews, and documentation. Data analysis techniques consist of data reduction, data presentation, and conclusion drawing. The results showed that 1) Management of drought emergency response through the “air disuntik resahpun terobati” program at the perusahaan air minum tirta mangkaluku kota Palopo from indicators of planning, organizing, and supervision can be said to be effective, but the implementation indicators cannot be said to be effective, seen from the absence of a definite scheme in its implementation, the uncertainty of time in the distribution process due to problems with the distance or location of water sources that are quite far away and non-technical problems, and the limitations of the fleet require assistance from related parties. 2) Supporting factors such as support from related parties, a clear organizational structure and employee motivation in providing services to the community so that the services provided can be maximized. The inhibiting factors are the lack of community awareness and the distance of distribution which is quite far so that it causes uncertainty in time.